2019
DOI: 10.1101/669135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early-Stage Ocular Hypertension Alters Retinal Ganglion Cell Synaptic Transmission in the Visual Thalamus

Abstract: 27Axonopathy is a hallmark of many neurodegenerative diseases including glaucoma, where elevated 28 intraocular pressure (ocular hypertension, OHT) stresses retinal ganglion cell (RGC) axons as they exit 29 the eye and form the optic nerve. OHT causes early changes in the optic nerve such as axon atrophy, 30 transport inhibition, and gliosis. Importantly, many of these changes appear to occur prior to irreversible 31 neuronal loss, making them promising points for early diagnosis of glaucoma. It is unknown whe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 95 publications
3
16
1
Order By: Relevance
“…We previously demonstrated that during a modest and sustained ocular hypertension, a key risk factor for glaucoma, vesicle release probability in the retinogeniculate synapse was increased (Bhandari et al, 2019). Although the extent of injury to the optic nerve is more severe in the present study, our results here present an interesting contrast to results from ocular hypertension.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…We previously demonstrated that during a modest and sustained ocular hypertension, a key risk factor for glaucoma, vesicle release probability in the retinogeniculate synapse was increased (Bhandari et al, 2019). Although the extent of injury to the optic nerve is more severe in the present study, our results here present an interesting contrast to results from ocular hypertension.…”
Section: Discussioncontrasting
confidence: 75%
“…Additionally, we have shown that in ocular hypertension, dLGN TC neuron dendritic complexity is reduced, especially in regions proximal to the TC neuron somata, where they receive retinal inputs (Bhandari et al, 2019). Findings from the current experiments indicate that similarly, there is a reduction in dendritic complexity proximal to the TC neuron somata, and these changes are prominent and significant by 14 days post-enucleation.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations